MUSEUM ARSITEKTUR JAKARTA DI KAWASAN MEDAN MERDEKA TIMUR - Nicholas Nicholas; Maria Veronica Gandha (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2019)
As time went on, the Museum in the city of Jakarta was still limited. The works exhibited remain the same and tend not to be interactive. Most museums in Jakarta try to show the historical side of Dutch colonialism and their heritage. but there is no museum that discusses how architecture in the city of Jakarta has developed rapidly until now and left its story or history. In the historical exposures of its growth, where the city government alternates and the conditions of its society are very diverse. But in its journey to a more modern era, there needs to be a change to the concept of the museum. The decline in the number of visits to the museum should be a concern that the millennial generation has begun to abandon the trend of traveling to museums because the museum is considered too old and undeveloped. The presence of the Jakarta architecture museum tells the story of the architectural journey of the city of Jakarta which has developed since the Dutch colonial era to the present. The design of the Museum which is located in the East Merdeka area is directly adjacent to the old building which has historical value, the Immannuel Church and the National Gallery; In addition, this region is connected in one tourism path that is being developed, from the Istiqlal Mosque and the Cathedral Church (which has historical architectural value) to the Proclamation Monument on the Proclamation Road. With a relationship between two destination points. The project also interacts with its surroundings as a comfortable place with open space for the surrounding community. The general program is supported by space 3.0 in the form of amphitheater, which can be accessed by various groups both horizontally and vertically. This project is expected to increase the insight and interest of visitors to study architecture and its role in building cities. AbstrakSeiring berjalanya waktu, Museum di kota Jakarta masih tetap terbatas. Karya karya yang dipamerkan tetap sama dan cenderung tidak interaktif. Kebanyakan museum di Jakarta mencoba menampilkan sisi historis dari penjajahan Belanda dan peninggalannya. namun belum ada museum yang membahas bagaimana arsitektur di kota Jakarta berkembang pesat sampai sekarang dan meninggalkan cerita atau sejarahnya. Dalam paparan sejarah pertumbuhannya, dimana pemerintah kotanya silih berganti dan kondisi masyarakatnya sangat majemuk. Namun dalam perjalanannya menuju era yang lebih modern, perlu adanya sebuah perubahan terhadap konsep museum. Menurunya angka kunjungan ke museum harus menjadi perhatian bahwasanya generasi milenial mulai meninggalkan tren berwisata ke museum karena museum dinilai terlalu tua dan tidak berkembang. Hadirnya museum arsitektur Jakarta bercerita gambaran perjalanan arsitektur kota Jakarta yang berkembang sejak zaman penjajahan Belanda hingga saat ini. Perancangan Museum yang terletak di kawasan Merdeka Timur berbatasan langsung dengan bangunan tua yang memiliki nilai sejarah, Gereja Immannuel dan Galeri Nasional; Selain itu kawasan ini terhubung dalam satu jalur pariwisata yang sedang di kembangkan, dari Masjid Istiqlal dan Gereja katedral (yang mana memiliki nilai historis arsitektur) hingga Tugu Proklamasi di jalan Proklamasi. Dengan adanya satu hubungan lingkage antar dua titik tujuan. Proyek ini juga berinteraksi dengan sekitarnya sebagai tempat yang nyaman dengan ruang terbuka untuk masyarakat sekitar. Program kemduian didukung dengan ruang 3.0 yang berupa amphiteather, dimana dapat di akses oleh berbagai kalangan baik secara kelas horizontal maupun vertikal. Proyek ini diharapkan dapat menambah wawasan maupun minat pengunjung untuk mempelajari arsitektur dan peranannya dalam membangun kota.